Comparison Of The Effectiveness Of Pear (Pyrus Communis) And Minute (Cucumis Sativus L) On Ph Saliva At The Panti Asuhan Cinta Kasih Foundation Teluk Dalam In 2021 - Molek Molek; Idamawati Nababan; Anna Maria (Institute of Computer Science (IOCS), 2022)
Caries is a common dental and oral disease. The main etiology of caries is plaque. Chewing fibrous fruits can prevent plaque accumulation, by increasing the pH of saliva, one of which is eating pears and cucumbers. The purpose of this study was to determine the difference in the effectiveness of consuming pears with cucumbers on increasing salivary pH at the Cinta Kasih Orphanage Foundation, Teluk Dalam District. This type of research is a quasi-experimental design with a pretest and posttest control group. The number of samples is 60 people who live in the Cinta Kasih Orphanage. Data were analyzed by statistical test T Test. Based on the results of the statistical paired t test, the average salivary pH before chewing pears was 6.94±0.53 after 7.44±0.42 with a mean of 0.50±0.11. Meanwhile, the average pH of saliva before chewing cucumber was 6. 81±0.22 after 7.02±0.16 with a mean of 0.16±0.21. The results of the independent statistical test t test obtained p values = 0.007 and 0.037, which means that there is a difference between chewing pears and cucumbers in increasing salivary pH. The conclusion of this study is that consuming pears has a higher effectiveness than cucumbers in increasing salivary Ph.